Multiple Rad52-Mediated Homology-Directed Repair Mechanisms Are Required to Prevent Telomere Attrition-Induced Senescence in Saccharomyces cerevisiae - Claussin, Clémence (PLoS Genet, 2016)
Most human somatic cells express insufficient levels of telomerase, which can result in telomere shortening and eventually senescence, both of which are hallmarks of ageing. Homology-directed repair (HDR) is important for maintaining proper telomere function in yeast and mammals. In Saccharomyces cerevisiae, Rad52 is required for almost all HDR mechanisms, and telomerase-null cells senesce faster in the absence of Rad52. However, its role in preventing accelerated senescence has been unclear. In this study, we make use of rad52 separation-of-function mutants to find that multiple Rad52-mediated HDR mechanisms are required to delay senescence, including break-induced replication and sister chromatid recombination. In addition, we show that misregulation of histone 3 lysine 56 acetylation, which is known to be defective in sister chromatid recombination, also causes accelerated senescence. We propose a model where Rad52 is needed to repair telomere attrition-induced replication stress.